How to get ahead : a proven 6-step system to unleash your personal brand and build a world-class network so opportunities come to you - Slayback, Zak (McGraw-Hill Education, 2019)
Turbocharge your professional success and accelerate your career. This practical guide cuts the fluff and gives you real, tangible, actionable steps you can take to build your own world-class network. Even if you think the terms "personal branding" or "networking" sound sleazy, How to Get Ahead teaches you how to earn more, learn more, get more done, and set yourself up for long-term career success. THIS PROVEN, SIX-STEP SYSTEM TEACHES YOU HOW TO: " Stop spinning your wheels and set professional goals that you can actually achieve." Identify, reach out to, and learn from mentors, teachers, and advisors to shave years off your learning and avoid painful mistakes." Eliminate overwhelm and burnout through a personalized project management system Identify and signal your skills and expertise to unleash your own personal brand." Discover The "Seven Deadly Sins of Networking" that kill your chances of building a world-class network- and how to avoid them." Tap into your own personal network and get introductions influential people-even if you hate "networking." " Make people want to work with you - even if you hate "pitching." Whether you're an employee, a business owner, an academic, a student, or an aspiring "digital nomad," this book gives you the steps to set up your own system for professional success